Prolegomena zur Pädagogik des gespaltenen Subjekts Ein notwendiger RISS in der Sonderpädagogik - Langnickel, Robert (Schriftenreihe der DGfE-Kommission Psychoanalytische Pädagogik, 2021)
The book aims to lay the prolegomena or the general systematic foundations of a pedagogy of the split subject for psychoanalytic pedagogy in general and for special education in particular. It examines the transferability and relevance of concepts of structural psychoanalysis by Lacan, Mannoni and Dolto for dealing with children and adolescents in psychosocial impairments to current pedagogical practices. The methodological approach to the research object is triangulated firstly through structural psychoanalytic hermeneutics, secondly through case vignettes and thirdly through dispositif analysis.